Cost-effectiveness analysis of the combination of low-dose nivolumab with triple metronomic chemotherapy for advanced head and neck squamous cell carcinoma in China - Cao, Yingdan; Shi, Fenghao; Wei, Xiaoxia; Han, Sheng; Fang, Yu (Frontiers in Oncology, 2025)
BackgroundThe combination of low-dose nivolumab with triple metronomic chemotherapy (TMC-I) proposes a novel approach, potentially enhancing patient prognosis while mitigating financial barriers. The purpose of this study was to compare the cost-effectiveness of TMC-I compared to triple metronomic chemotherapy (TMC) in advanced head and neck squamous cell carcinoma (HNSCC) patients in China, the largest developing country.MethodsA partitioned survival model (PSM) was developed based on a randomized clinical trial. Costs and utility were derived from open-access databases and literatures. The primary outcome was incremental cost-effectiveness ratio (ICER). A willingness-to-pay (WTP) threshold of ¥44,679/QALY based on supply-side and ¥134,037/QALY based on demand-side were set. Sensitivity analyses and scenario analysis were conducted; subgroup analyses were also included.ResultsTMC-I yielded an additional 0.41 quality-adjusted life years (QALYs) while increasing costs by ¥47,346.98 relative to TMC, leading an ICER of ¥116,374.22/QALY. In scenario analysis which the utilities calculated by the time-to-death (TTD) were adopted, the results showed that the ICER was ¥114,795.25/QALY. In the probabilistic sensitivity analysis, the probabilities that TMC-I was cost-effective at thresholds of ¥134,037/QALY, ¥44,679/QALY gained were 60.9%, 9.4%, respectively. Subgroup analysis results indicated TMC-I was dominated vs. TMC for patients with no previous taxane and PD-L1 score >50.ConclusionFor Patients with recurrent or newly diagnosed advanced head and neck squamous cell carcinoma, TMC-I is cost-effective at a WTP thresholds of ¥134,037/QALY and is not cost-effective when the WTP thresholds was ¥44,679/QALY compared with TMC.